The key technologies of millimeter wave MIMO communication system in space information network - Xin-ying MA; Zhi CHEN; Si MA; Jun FANG (Tongxin xuebao)
With the rapid development of space information network and the increasing expansion of mankind activity,the requirements of communication quality become higher between mobile satellites and earth stations.In order to meet the demands of high data rate,large capacity and broadband real-time communication,applying millimeter wave frequency band to mobile satellite communication system has attracted great attention.Beamforming,tracking and channel estimation were introduced in millimeter wave MIMO system to fully understand the challenges of space information network which will face in the future.